How do EFL university student-writers prepare their draft? An analysis of writing strategy use in EFL writing instruction - Sundari, Hanna; Febriyanti, Rina Husnaini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The use of writing strategy across writing levels in a virtual EFL writing course was still rarely found in the literature. To fill this gap, therefore, this current research aims at exploring writing strategy in EFL writing instruction. Informed by a research framework of descriptive case study, university student-writers who regularly attended a virtual academic writing course filled out the online writing strategy inventory (Yang & Plakans, 2012) and submitted the argumentative essays. The findings show that the writing strategy was diverse across levels. At the stage of before drafting the essay, all student-writers reread task requirement and understood the type of essay and organization, searched for valid references, and tried to avoid plagiarism. Moreover, student-writers with higher levels also summarized ideas, analyzed sentences and contents, and made writing plan. At drafting the essay, they double checked the requirement, revised the essay, reread the essay and the sample texts, and provided valid arguments. However, student-writer with lowest level was not used those strategies. At the stage of after drafting, student-writers in all levels applied similar several writing strategies. However, not all of them added new points from sample texts, references, and lecture. To the student-writer with the lowest level, several writing strategies were not applied. This may indicate that student-writers with higher levels have writing awareness to use writing strategy effectively to improve their essay. Then, it can be drawn a conclusion that the more writing strategies used during drafting the essay, the more score and the higher quality of the essay was possibly achieved.